2016
DOI: 10.1111/tid.12512
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput sequencing of cerebrospinal fluid for diagnosis of chronic Propionibacterium acnes meningitis in an allogeneic stem cell transplant recipient

Abstract: High-throughput metagenomic shotgun sequencing revealed P. acnes as the cause of chronic meningitis that had eluded conventional attempts at diagnosis. Treatment directed at this organism resulted in cure of the infection and clinical improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Metagenomics to screen for unclear or unknown infectious etiologies has been recently applied in several clinical cases to support routine diagnostics (Cordey et al, 2014 ; Naccache et al, 2015 ; Ortiz Alcántara et al, 2015 ; Kawada et al, 2016 ; Wylie et al, 2016 ; Lewandowska et al, 2017 ; Ruppé et al, 2017 ). Like for every eukaryotic sample, NGS analyses in clinical samples are greatly affected by a very low pathogen-to-host genome ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metagenomics to screen for unclear or unknown infectious etiologies has been recently applied in several clinical cases to support routine diagnostics (Cordey et al, 2014 ; Naccache et al, 2015 ; Ortiz Alcántara et al, 2015 ; Kawada et al, 2016 ; Wylie et al, 2016 ; Lewandowska et al, 2017 ; Ruppé et al, 2017 ). Like for every eukaryotic sample, NGS analyses in clinical samples are greatly affected by a very low pathogen-to-host genome ratio.…”
Section: Discussionmentioning
confidence: 99%
“…For adequate patient management, improved identification of CNS infection etiologies to enable targeted therapy is indispensable. Metagenomics was recently used to assist infectious disease diagnostics, also for meningo-/encephalitis (Cordey et al, 2014 ; Naccache et al, 2015 ; Ortiz Alcántara et al, 2015 ; Kawada et al, 2016 ; Wylie et al, 2016 ; Lewandowska et al, 2017 ; Ruppé et al, 2017 ). Shotgun metagenomics, that sequences all nucleic acids (NA) in a given sample, has the potential to identify known but mutated (evading qPCR detection), unexpected, and previously undetected pathogens or mixed infections (Palacios et al, 2008 ; Basmaci et al, 2011 ; Smits et al, 2013 ; Tan le et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite some advantages, WMGS is not routinely used in clinical microbiology. Few clinical single-patient studies investigated with metagenomics have been reported in the literature and they mostly concern viral acute encephalitis [ 5 ], infective endocarditis [ 6 ], or bacterial meningitis [ 7 , 8 ]. There are several reasons why WMGS has not yet been extensively used in routine analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Brain abscess, subdural or epidural empyema, and shunt meningitis are common P. acnes-related CNS infections that are successfully treated by antibiotics, sometimes in combination with surgical interventions such as drainage and debridement [7][8][9]. By contrast, P. acnes causes meningitis without neurosurgical procedures in both immunocompromised [22] and immunocompetent patients [10][11][12][13][14]. In P. acnes infection cases without trauma or surgical procedures, the paths by which P. acnes invades the CNS putatively include (1) hematogenous routes via the diploic veins from the hair follicles or sebaceous glands of the scalp or (2) invasion from adjacent inflammation such as sinusitis, orbititis, and otitis media [4].…”
Section: Discussionmentioning
confidence: 99%